Broke But Not Bankrupt: Consumer Debt Collection in State Courts - Richard M. Hynes (My University, 2016)
Virginia, with a population of about seven million, has averaged more than a million civil filings a year since the late 1980s. The overwhelming majority of these filings seek to collect debts from consumers, and most judgments go unpaid. Despite this apparent insolvency, civil litigation appears to be only tenuously related to consumer bankruptcy whether one looks at Virginia or at the nation as a whole. Nationally, the non-business bankruptcy filing rate rose by more than 350% between 1980 and 2002, while the civil filing rate rose by about 12%. Prior research suggests that relatively few bankrupt debtors have been sued by their creditors in state court, that most bankrupt debtors and drawn from the middle class, and that bankrupt debtors own homes at nearly the same rate as the general population. This Article finds that few civil defendants file for bankruptcy, that civil litigation is concentrated in cities and counties with lower socio-economic characteristics, and that civil defendants in Virginia have a significantly lower rate of homeownership than the general population. In other words, the bankruptcy statistics exclude many defaulting and insolvent consumers, and these consumers may be disproportionately drawn from the more disadvantaged segments of society.